Developing the coordination skills of young players through special exercises - Valiyev Farrukh Nigmatjonovich; Rikhsiev Dilshod Shavkatovich (Periodica Journal, 2022)
In essence, we all know that sport is a guarantee of health. Therefore, sports are becoming more popular in Uzbekistan. The fact that the number of our compatriots living a healthy lifestyle is growing day by day is also a proof of our opinion. This article discusses the development of young players' coordination skills through special exercises.
Keywords: coordination ability; general and special physical training; physical qualities